Consideration on Disaster Recovery System to Improve Resilience of Frequent-landslide Dangerous Area. (9th May 2016) - Kachi, Noriyasu; Kajimoto, Ryosuke; Tsukahara, Kenichi; Akiyama, Yuki
Abstract: In Japan, the torrential rain related disaster, which was caused by climate change, has increased in recent years. Especially, the numerous landslides due to the torrential rain have frequently occurred in the urban fringe of many Japanese cities. For example, the landslides due to the Northern Kyushu Torrential Rain in July of 2012 caused extensive damage to the residential areas in urban fringe of Aso-shi in Kumamoto Prefecture. The landslides due to the torrential rain in 1990 caused extensive damage to the almost same residential areas in urban fringe as the landslides in July of 2012. This historical data implies that the landslide will cause considerable damage to the same residential areas when the historical maximum torrential rain occurs in the future. It seems to be desired that the residents, which live in landslide-damaged areas, to migrate to safe areas. However, the basic principle for the recovery of residential area from a landslide disaster is restoring the damaged area to its condition before the disaster under the current Japanese institutions for the post-disaster restoration, which does not allow their migration to other safe area against disaster. It is preferable for most residents damaged by landslide-disaster to continue to live in the same residential area where they have lived until landslide-disaster occurred, in terms of their economic aspects. This results in the repeated landslide-disaster damage to the same residential area. The subsidy scheme under the current Japanese disaster recovery system should be changed to the subsidy scheme, which can allow the residents damaged by landslide-disaster to migrate to safe residential area. This subsidy scheme, which can allow the residential migration, has financial advantage of the reduction of total social cost by preventing repeated damage. The case study of Aso-shi in Kumamoto prefecture indicated that this scheme was financially feasible.